Neural relation extraction: a review - Aydar, Mehmet; Bozal, Ozge; Ozbay, Furkan (Tubitak Scientific & Technological Research Council Turkey, 2021)
Neural relation extraction discovers semantic relations between entities from unstructured text using deep learning methods. In this study, we make a clear categorization of the existing relation extraction methods in terms of data expressiveness and data supervision, and present a comprehensive and comparative review. We describe the evaluation methodologies and the datasets used for model assessment. We explicitly state the common challenges in relation extraction task and point out the potential of the pretrained models to solve them. Accordingly, we investigate additional research directions and improvement ideas in this field.
Keywords: Neural relation extraction; deep learning; pretrained model; distant supervision; Computer Science; Engineering